The enigma of solitary necrotic nodule of the liver. Issue 4 (9th November 2012) - Pananwala, Hasitha; Pang, Tony C.; Eckstein, Robert P.; Hudson, Bernard J.; Newey, Allison; Samra, Jaswinder S.; Hugh, Thomas J.
Abstract Background Solitary necrotic nodule of the liver (SNNL) is a rare benign lesion with an uncertain aetiology. There are no typical diagnostic clinical or radiological features, and this lesion is usually detected incidentally during imaging for other purposes. Methods We describe the clinical and radiological findings in three patients with histologically confirmed SNNL. The pertinent presenting features were documented and subsequent serological testing for parasites was performed. Results All three patients underwent resection because it was not possible to exclude a solitary malignancy on preoperative imaging. All three nodules had a serpiginous shape with areas of necrosis that showed marked staining for eosinophil granules. However, no viable parasites were seen in any specimen. There were no specific radiological features that were present in all three patients. Two patients had travelled to areas where parasitic infections are endemic and one patient had an eosinophilia on presentation. The histopathological findings in conjunction with the clinical presentation suggest that SNNL may be parasitic in origin. Conclusion The diagnosis of SNNL is usually made after surgical excision. A preoperative diagnosis is difficult to make even with the use of multiple imaging modalities. The clinical and histopathological findings described in our three patients suggest that a transient parasitic infection is likely to be the cause in many cases. A history of potential exposure to parasites and serological testing for an eosinophilia or parasitic antibodies may help make the diagnosis of SNNL without the need for resection.